A Study on The Vocabulary Knowledge of the Second Grade Students of Senior High School - Sukma Indriani; Supriusman Supriusman; M. Syarfi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research used descriptive-quantitative design which aims to find out the vocabulary knowledge level of the second year students of SMAN 1 Kuantan Mudik. The sample of this research is class XI MIPA 3 of the second year students of SMAN 1 Kuantan Mudik which were chosen by using cluster random sampling technique. The number of the students is 32 students. The students were given The Updated Vocabulary Test (UVLT) that is adopted by Webb, et.al (2017). The result shows that the level of vocabulary knowledge of the second-grade students of SMAN 1 Kuantan Mudik is still below the threshold needed for reading or daily conversation. There were only 2 students who reached the mastery score at the 1000 level, and none of them at the 2000-5000 level. High frequency vocabulary will have a greater influence on students, according to Webb (2017). Teachers are recommended to increase studentsâ€™ vocabulary knowledge through reading activities and additional vocabulary tasks.Â